2007
DOI: 10.1002/cmdc.200600242
|View full text |Cite
|
Sign up to set email alerts
|

Homology Modeling of the Serotonin Transporter: Insights into the Primary Escitalopram‐binding Site

Abstract: The serotonin transporter (SERT) is one of the neurotransmitter transporters that plays a critical role in the regulation of endogenous amine concentrations and therefore is an important target for therapeutic agents affecting the central nervous system. The recently published, high resolution X-ray structure of the closely related amino acid transporter, Aquifex aeolicus leucine transporter (LeuT), provides an opportunity to develop a three-dimensional model of the structure of SERT. We present herein a homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 58 publications
(82 reference statements)
2
51
0
Order By: Relevance
“…In LeuT Aa , TMs 1, 3, 6, and 8 form the leucine binding pocket. Biochemical analyses and homology modeling of SERT proteins predict a similar binding pocket for 5-HT (32)(33)(34)(35)(36). Consistent with these models, pre-structure studies identified residues in hSERT TMs 1 and 3 that confer high affinity interactions and ligand selectivity to substrates and antagonists.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…In LeuT Aa , TMs 1, 3, 6, and 8 form the leucine binding pocket. Biochemical analyses and homology modeling of SERT proteins predict a similar binding pocket for 5-HT (32)(33)(34)(35)(36). Consistent with these models, pre-structure studies identified residues in hSERT TMs 1 and 3 that confer high affinity interactions and ligand selectivity to substrates and antagonists.…”
mentioning
confidence: 56%
“…Because hSERT TM6 is predicted to lie adjacent to and share topology with TM1 (27,(32)(33)(34)(35)(36), we explored potential contributions of TM6 to the interactions of 5-HT, MDMA, and cocaine via an assessment of their ability to protect hSERT C109A Cys mutants from inactivation by MTSET and biotinylation with MTSEA-biotin. Before initiation of protection experiments, we examined the sensitivity of each Cys mutant to MTSET at 0.1, 1, and 10 mM to ensure we were using a concentration of MTSET appropriate for detecting either protection or exposure.…”
Section: G338c Appears To Stabilize An Open Conformation Of Hsert-mentioning
confidence: 99%
“…Currently, there is no existing crystal structure of SERT; however, a number of homology models of hSERT are available which were constructed using the bacterial leucine transporter (LeuT) as a template 32,33 . For this study the homology model of hSERT constructed by Jørgensen et al (2007) was used 33 . A number of previous studies have identified key binding residues involved in the binding of SERT ligands [33][34][35][36] .…”
Section: Molecular Modellingmentioning
confidence: 99%
“…For this study the homology model of hSERT constructed by Jørgensen et al (2007) was used 33 . A number of previous studies have identified key binding residues involved in the binding of SERT ligands [33][34][35][36] . 5-HT, the natural substrate of SERT, and amphetamines such as 4-MTA interact with residues Ala96, Asp98 and Phe335 via binding of the protonated amine (Fig.…”
Section: Molecular Modellingmentioning
confidence: 99%
“…For some nontransportable, competitive drugs like the SSRI citalopram, convincing biochemical evidence for a primary binding site that overlaps with that of the substrate 5-HT 148 was acquired before the LeuT structure was published but is now also supported by LeuT-based homology models of SERT. 149 For other drugs, like cocaine, a combination of LeuT-based homology models and mutagenesis on DAT suggests that the binding sites of dopamine and cocaine also overlap. 150 Although these studies are reassuring and probably identify the correct antagonist binding sites, they still do not detail the conformational changes predicted to be associated with competitive inhibition and an extracellular inhibitor like cocaine [151][152][153] or the GAT1 inhibitor SKF100330, 154 i.e., stabilization of an open-to-out state.…”
Section: Mechanism Of Inhibitionmentioning
confidence: 99%